Role of molecular properties of ulvans on their ability to elaborate antiadhesive surfaces. Issue 3 (13th June 2014) - Gadenne, Virginie; Lebrun, Laurent; Jouenne, Thierry; Thebault, Pascal
Abstract Antiadhesive properties of polysaccharides (such ulvans) once immobilized on a surface are described in the literature but the parameters governing their antifouling properties are not yet well identified. In the present study, the relationship between molecular parameters of ulvans and the inhibition of bacterial adhesion was investigated. To this aim, various ulvans were grafted on silicon wafers under two different experimental immobilization conditions. Results showed that the experimental immobilization conditions and the polysaccharides molecular weight led to specific layer conformations which exhibited a key role in the surface antiadhesive properties. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1021–1028, 2015.